CORRELATION BETWEEN CALCIUM BENTONITE CONCENTRATION AND PARAFFIN WAX TO THE HARDNESS OF CARVING WAX: HUBUNGAN ANTARA KONSENTRASI KALSIUM BENTONIT DENGAN PARAFIN MALAM TERHADAP KEKERASAN MODEL MALAM - Widjijono (Dentika: Dental Journal, 2009)
The carving wax composes many natural or synthetic waxes and sometimes filler is added physical and mechanicalproperties. The aim of this study was to determine the correlation of concentration Ca-bentonite carving wax compositionand the hardness. The paraffin, carnauba wax, bees wax, Ca-bentonite, and inlay wax were used in this research. Thecarving wax compositions were made of paraffin, Ca-bentonite, carnauba wax, and bees wax ratio (% weight): 50:20:25:5(KI), 55:15:25:5 (KII), 60:10:25:5 (KIII), 65:5:25:5 (KIV), 70:0:25:5 (KV). All components were melted, then pouredinto hardness moulds (n=5). The carving wax properties were tested of their hardness by penetrometer (Setamatic, UK).Data were analyzed statistically by regression test and linearity by Anova. The results showed that regression linearsignificantly (p<0.05) and the regression of equation was Y = 18.365-50.940 X with coefficient regression of (R) = 0.922(p<0,05) and determinant factor 84.9 percent. The conclusion of this study was the adding of Ca-bentonite on thecomposition of carving wax improved its hardness with the significant linearity (p<0.05).